PERBEDAAN HUKUM PERBURUHAN DI NEGARA DENGAN SISTEM HUKUM CIVIL LAW DAN COMMON LAW STUDI KASUS SINGAPURA DAN INDONESIA (Lex Jurnalica, 2016)
AbstractIn the field of labor law, there are two kinds of sources of law, namely: an autonomous legal norms and heteronomiclegal norms. The first is the legal provisions stipulated by the parties engaged in a working relationship that is between the workers or Trade Unions with Employers or Employers organizations. For example the Employment Agreement, the Company Regulations and Collective Labor Agreement. The second is the legal provisions stipulated by Third Parties outside the parties engaged in a working relationship. Legislation in the field of labor prevailing in Indonesia, among others, is Law No. 13 of 2003 and Law No. 02 of 2004. If the above legal traditions associated with both types of sources of labor law, it is in those countries that embrace Common Law tradition, the main source of labor laws in general are Autonomous norms. In the countries of the Civil Law legal tradition, in general are heteronomic norms. Labor law is not the kind of law that is neutral and independent, so that the necessary government involvement as a safeguard against the weak position of workers. Singapore (Common Law) have labor laws that the Employment Act 1968. The Employment Act 1968 is a refinement on various ordinances created by the colonial ruler (Britain), which are The Labor Ordonance 1957, The Shop Assistants Employment Ordinance 1957 and The clerck's Employment Ordinance 1957. Keywords: Labor law, civil law, common law, Indonesia, SingaporeÂ AbstrakDi bidang Hukum Perburuhan terdapat dua macam sumber hukum yaitu: kaedah hukum otonom dan kaedah hukum heteronom. Yang pertama adalah ketentuan-ketentuan hukum yang ditetapkan oleh para pihak yang terikat dalam suatu Hubungan Kerja yaitu antara buruh atau Serikat Buruh dengan Pengusaha atau Organisasi Pengusaha. Misalnya Perjanjian Kerja, Peraturan Perusahaan dan Perjanjian Kerja Bersama. Yang kedua adalah ketentuan-ketentuan hukum yang ditetapkan oleh Pihak Ketiga di luar para pihak yang terikat dalam suatu Hubungan Kerja. Peraturan Perundang-undangan di bidang perburuhan yang berlaku di Indonesia, antara lain adalah UU No. 13 Tahun 2003 dan UU No. 02 Tahun 2004.Jika kedua tradisi hukum tersebut di atas dikaitkan dengan kedua jenis sumber hukum perburuhan, maka di negara-negara yang menganut tradisi hukum Common Law, sumber hukum perburuhan yang utama pada umumnya adalah kaedah otonom. Di negara-negara bertradisi hukum Civil Law, pada umumnya kaedah heteronom.Hukum Perburuhan bukanlah jenis hukum yang netral dan independen, sehingga diperlukan keterlibatan pemerintah sebagai upaya perlindungan terhadap buruh yang lemah kedudukannya. Singapura (Common Law) memiliki undang-undang ketenagakerjaan yaitu The Employment Act 1968. The Employment Act 1968 ini merupakan penyempurnaan atas berbagai ordonansi yang dibuat oleh penguasa colonial (Inggris), diantaranya adalah The Labor Ordonance 1957, The Shop Assistants Employment Ordinance 1957 dan The Clerckâ€™s Employment Ordinance 1957.Â Kata Kunci : Hukum perburuhan, civil law, common law, Indonesia, Singapura